Secure bits through queues - Dunn, B.P.; Bloch, M.; Laneman, J.N. (2009 IEEE Information Theory Workshop on Networking and Information Theory, 2009)
We investigate the idea of providing information-theoretic security at the network and data link layers by exploiting the timing information resulting from queuing of packets between a source, an intended receiver, and other users in a network. Specifically, we consider the secure transmission of messages by encoding them onto the interarrival timing of packets that enter parallel queues. By leveraging recent results on the secrecy capacity of arbitrary wiretap channels, achievable secrecy rates are obtained. We also show that equivalent secrecy rates can be achieved using a deterministic encoding strategy, which provides an example contrasting the fact that for many memoryless channels a stochastic encoder is required to achieve non-zero secrecy rates.